A Review on Bio-alcohol as Green Energy (International Journal of Innovative Research in Computer Science & Technology, 2020)
Bioethanol has grown into a large business,  and it seems that it will continue to grow in the foreseeable  future. Although certain challenges, such as rivalry among  bioethanol and human food, bioethanol is widely  recognised as a sustainable and renewable new energy  sources. Bioethanol has the potential to be a good source  of basic raw materials. Dehydrating ethanol yielded  ethylene, the most important organic biochemical raw  material. Throughout WWII, as the petrochemical sector  boomed, industrial ethanol was mostly produced through  hydration of ethylene. Humans should expect bioethanol to  become a new source of simple organic raw materials, and  other higher-value fine and specialized chemicals, rather  of merely a fuel, now that it has entrenched itself as a  substantial fuel mixture. Each day, a slew of new  bioethanol enterprises open their doors. More research into  bio - ethanol as either a starting raw chemical source is  needed.
Keywords: Bioethanol; Lignocellulose; Cellulases; Pretreatment; Ethanologens; Vacuum Cycling